Integrasi Pemasaran Islam dan Tanggung Jawab Sosial Perusahaan di Era Digital: Analisis dalam Perspektif Maqashid Syariah - Syahvira Salsabilla Putri; Ismatul Khayati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the implementation of Islamic marketing and digital-based Corporate Social Responsibility (CSR) at Pegadaian Syariah Surabaya from the perspective of maqashid sharia and assess how the integration of the two supports the sustainability of the institution and public trust. The background of the study departs from the development of digital technology that requires Islamic financial institutions to maintain transparency, fairness, data security, and sharia compliance in all marketing activities and social programs. The research method uses a descriptive qualitative approach through in-depth interviews, participatory observation, and documentation analysis on digital services and CSR activities of Pegadaian Syariah. The results show that digital Islamic marketing not only functions as a promotional tool, but also as a sharia education medium that upholds the values ​​of shidq, amanah, and maslahah, thereby supporting hifz al-din, hifz al-mal, and hifz al-‘aql. Meanwhile, the implementation of CSR covers the fields of religion, health, education, and empowerment of MSMEs that are in line with the five dimensions of maqashid sharia. The integration of Islamic marketing and CSR creates a strategic synergy that increases public trust, strengthens the institution's legitimacy, and ensures the sustainability of Pegadaian Syariah in the digital era. This research provides theoretical contributions regarding maqasid-based marketing and CSR strategies, as well as practical recommendations for strengthening sharia governance and digital education programs.